2018
DOI: 10.1021/acs.jafc.7b05992
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Environmental and Developmental (or Metabolic) Control of Seed Mass by Sugar and Ethylene Metabolisms in Arabidopsis

Abstract: In higher plants, seed mass is an important to evolutionary fitness. In this context, seedling establishment positively correlates with seed mass under conditions of environmental stress. Thus, seed mass constitutes an important agricultural trait. Here, we show loss-of-function of YODA (YDA), a MAPKK Kinase, and decreased seed mass, which leads to susceptibility to drought. Furthermore, we demonstrate that yda disrupts sugar metabolisms but not the gaseous plant hormone, ethylene. Our data suggest that the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The regulatory network of genes that involved in the growth and development of maternal and zygotic tissues is crucial for seed size/weight. Recently, extensive studies have been made in establishing what metabolism molecule integrates plant responses to environmental stresses into the control of seed size and weight (Meng et al, 2018). It has been reported that soluble sugar accumulation can influence seed size via AN3-YDA (ANGUSTIFOLIA3-YODA) gene cascade and integration of environmental and development (or metabolic), and control seed weight by sugar and ethylene metabolisms in Arabidopsis (Meng et al, 2017;Meng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory network of genes that involved in the growth and development of maternal and zygotic tissues is crucial for seed size/weight. Recently, extensive studies have been made in establishing what metabolism molecule integrates plant responses to environmental stresses into the control of seed size and weight (Meng et al, 2018). It has been reported that soluble sugar accumulation can influence seed size via AN3-YDA (ANGUSTIFOLIA3-YODA) gene cascade and integration of environmental and development (or metabolic), and control seed weight by sugar and ethylene metabolisms in Arabidopsis (Meng et al, 2017;Meng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive studies have been made in establishing what metabolism molecule integrates plant responses to environmental stresses into the control of seed size and weight (Meng et al, 2018). It has been reported that soluble sugar accumulation can influence seed size via AN3-YDA (ANGUSTIFOLIA3-YODA) gene cascade and integration of environmental and development (or metabolic), and control seed weight by sugar and ethylene metabolisms in Arabidopsis (Meng et al, 2017;Meng et al, 2018). The signaling pathways that may affect seed size and weight have been identified, including the ubiquitin-proteasome pathway, G-protein signaling, mitogen-activated protein kinase signaling, transcriptional regulators, HAIKU (IKU) pathway, and phytohormones .…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene also plays a role in modulating seed development. Compared with WT Arabidopsis , EIN3 mutants present increased seed size, likely by affecting embryo cell elongation (Meng et al, 2018). Ethylene is also reported to promote seed iron storage during Arabidopsis seed maturation, possibly through an EIN3‐ERF95‐FER1‐dependent signaling pathway (Sun et al, 2020).…”
Section: Agricultural Significance Of Ethylenementioning
confidence: 99%
“…Total RNA was extracted from tissues indicated in the figures by the TRIZOL reagent (Invitrogen), as has been described by Meng (2015) and Meng, Xu, Wan, and Wang (2018). SYBR green was used to monitor the kinetics of PCR product in real-time RT-PCR, as has been described by Meng (2015).…”
Section: Quantitative Pcrmentioning
confidence: 99%